Preparations for a European R&D roadmap for an inertial fusion demo reactor. (25th January 2021) - Norreys, P. A.; Ceurvorst, L.; Sadler, J. D.; Spiers, B. T.; Aboushelbaya, R.; Mayr, M. W.; Paddock, R.; Ratan, N.; Savin, A. F.; Wang, R. H. W.; Glize, K.; Trines, R. M. G. M.; et al.
Abstract : A European consortium of 15 laboratories across nine nations have worked together under the EUROFusion Enabling Research grants for the past decade with three principle objectives. These are: (a) investigating obstacles to ignition on megaJoule-class laser facilities; (b) investigating novel alternative approaches to ignition, including basic studies for fast ignition (both electron and ion-driven), auxiliary heating, shock ignition, etc.; and (c) developing technologies that will be required in the future for a fusion reactor. A brief overview of these activities, presented here, along with new calculations relates the concept of auxiliary heating of inertial fusion targets, and provides possible future directions of research and development for the updated European Roadmap that is due at the end of 2020. This article is part of a discussion meeting issue 'Prospects for high gain inertial fusion energy (part 2)'.